PENGGUNAAN STRATEGI ROLE PLAY DAN STRATEGI MODELING THE WAY DALAM PEMBELAJARAN AQIDAH AKHLAK TERHADAP HASIL BELAJAR SISWA KELAS IV DI MIN BAWAN BARABAI - Rusdiana Husaini; muzdhalifah muzdhalifah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2017)
This research aims to determine the learning outcomes of Aqeedah Akhlak for students who learn by implementing role play learning strategies for experimental class and modeling the way strategy for the control class and to know the difference between the use of role play strategy and modeling the way strategy for learning outcomes of Aqeedah Akhlak for students IV grade at MIN Bawan Barabai. This research used experimental method. The subject of the research is the fourth grade students at MIN Bawan Barabai academic year 2016/2017. IVA grade is as experimental group (using role play strategy) and IVB grade is as control group (using modeling the way strategy) .The material taught is morality story of Masyitah. The student's initial ability data is taken from the pretest and posttest values as the research data. The learning outcomes of Aqeedah Akhlak for IV grade students in MIN Bawan Barabai by using role play strategy (pretest 66 and average value of posttest 84.66). While learning result of Aqeedah Akhlak fourth grade student in MIN Bawan Barabai by using strategy of modeling the way (pretest average value 62 and posttest average value 80,66). Based on the test result with U test, it can be concluded that there is no significant difference between the use of role play strategy in experimental group and the use of modeling the way strategy in control group on learning outcomes of Aqeedah Akhlak for fourth grade students MIN Bawan Barabai.